Positive Psychotherapy Effect on Life Expectancy and General Health of Type 2 Diabetic Patients: A Randomized Controlled Trial - Mohammad Hossein Sorbi; Kheirollah Sadeghi; Masoud Rahmanian; Seyed Mojtaba Ahmadi; Hamid Reza Paydarfar (Iranian Journal of Diabetes and Obesity, 2018)
Objective: Diabetes is a chronic disease that influences mental and physical health. Regarding the importance of diabetic patients’ psychological status, this research studied the effect of group positive psychotherapy on life expectancy and general health of type 2 diabetic patients. Materials and Methods: This clinical-trial study was done on 30 type 2 diabetic patients in Kermanshah diabetes research center. The experimental and control groups were randomly selected. Data were gathered before and 10 weeks after intervention. Demographic, life expectancy and general health (GHQ) questionnaires were used for gathering data. SPSS-16 and Kolmogorov-Smirnov (K-S), Chi-square and analysis of covariance (ANCOVA) were used for analyzing data. Results: Results showed that group positive psychotherapy caused significant enhancement on life expectancy in intervention group than control group (P-value: 0.001). Although positive psychotherapy caused significant reduction on anxiety disorder and somatic symptoms in mental health, there was no significant difference of general health between two groups (P-value: 0.347). Conclusion: Positive psychotherapy was effective on increasing diabetic patients’ life expectancy. So this efficient psychotherapy can be used for increasing type 2 diabetic patients’ life quality.